137k views
0 votes
What is the solution to the given system of equations?

y=4x-3

y=-x-13



A: (-11, -2)



B: (-2, -11)



C: (-2, -15)



D: (-2, 5)

User Savagent
by
5.9k points

2 Answers

7 votes

Answer:

the answer is B

Explanation:

User Aegis
by
5.7k points
5 votes

y = 4x - 3 substitute it to the second equation y = -x - 13:

4x - 3 = -x - 13 add 3 to both sides

4x = -x - 10 add x to both sides

5x = -10 divide both sides by 5

x = -2

Substitute the value of x to the first equation:

y = 4(-2) - 3

y = -8 - 3

y = -11

Answer: B: (-2, -11)

User Allan Macmillan
by
5.5k points